Mekanisme Pertahanan diri Kaum Tarekat - Abd. Syakur (Islamica: Jurnal Studi Keislaman, 2010)
Sufi orders have been instrumental in the life of the Sufis as centers for spiritual training and education. In these centers the Sufis can elaborate their ideas, and apply them in real life. In the passages of time however, these orders were no longer considered simply as religious centers but also as social groupings consisting of people committed not only to practice the teaching of their religion but also to get involved in social problems. There are indeed many Sufi orders with different character and upbringing. But as a whole, a Sufi order is mechanism for the spiritual survival of its fellows. This paper tries to look at the other side of the matter and argues that a Sufi order is not only spiritual in its nature but is also social. It treats Sufi orders as a social body that functions socially to help the murids to survive socially and not spiritually. We believe that the extinction of some Sufi orders is due mainly to their inability to curb with social issues and not because of the nature of their spiritual teaching. The survival of any Sufi order in other words depends very much on its social mechanism and not on the strength of its spiritual dictum.